2002
DOI: 10.1111/j.1460-2466.2002.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment and Crime Drama: An Integrated Theory of Enjoyment

Abstract: The article proposes a theoretical framework in which moral reasoning about mediated crime and punishment is defined and combined with existing, affect-driven entertainment theory to yield an integrated theory of enjoyment. The authors analyze how crime dramas serve as statements about justice and then address how moral deliberation about the propriety of those statements impacts enjoyment. The authors report research findings to support the analysis of cognitive processing during crime dramas distinct from af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 35 publications
3
86
0
Order By: Relevance
“…Although no published research has explored motives for viewing programming featuring law and justice themes, several studies have explored the related question of what factors underlie the enjoyment of crime dramas. One predictor of such enjoyment is the perception that justice is served; when crime results in appropriate punishment, enjoyment increases (Raney, 2005;Raney & Jennings, 2002). Although individuals may vary in the degree to which they think an individual outcome on such a program represents justice, the depiction of justice seems to be a key element to the enjoyment of programs of this genre.…”
mentioning
confidence: 96%
“…Although no published research has explored motives for viewing programming featuring law and justice themes, several studies have explored the related question of what factors underlie the enjoyment of crime dramas. One predictor of such enjoyment is the perception that justice is served; when crime results in appropriate punishment, enjoyment increases (Raney, 2005;Raney & Jennings, 2002). Although individuals may vary in the degree to which they think an individual outcome on such a program represents justice, the depiction of justice seems to be a key element to the enjoyment of programs of this genre.…”
mentioning
confidence: 96%
“…Based on these judgments, positive affect is assumed to occur when "good" characters prevail, and when negative outcomes befall "bad" or disliked characters. Across a variety of genres, research has supported the assumption that viewers experience the greatest level of positive affect and enjoyment when the portrayed outcomes are perceived as just or correct (for an overview, see Raney & Bryant, 2002).…”
Section: Entertainment Gratifications Associated With the Experience mentioning
confidence: 99%
“…Entertainment theory research has found empirical support for the notion that individual differences impact both the experience of narratives and the strategies used to moderate moods (Raney & Bryant, 2002;Zillman, 2000b). argue that, in contrast to the text hegemony hypothesis of canon-oriented literature scholar Bloom (1994), situational factors of reading and individual differences in the reader affect the level of transportation.…”
Section: Transportation and Individual Differencesmentioning
confidence: 95%